Crossed Renal Ectopia without Fusion—An Unusual Cause of Acute Abdominal Pain: A Case Report - D. P. Ramaema; W. Moloantoa; Y. Parag (Case Reports in Urology)
Introduction. Crossed renal ectopia is a congenital anomaly which usually goes unnoticed as most cases are asymptomatic. The majority, 90% of these are fused. Case Presentation. We report an unusual presentation of a case of crossed renal ectopia without fusion. Our patient is a 16-year-old adolescent male, previously fit and healthy, who presented with acute onset of abdominal pain. The clinical suspicion was that of an abdominal aortic aneurysm. Computed tomography with intravenous contrast revealed nonfused crossed renal ectopia. Conclusion. Although renal ectopia is an uncommon cause of acute abdominal pain, there should be an index of clinical suspicion in previously healthy individuals presenting with acute abdominal pain.